Overview of Pakistan’s Electricity Crisis, Generation-Mix and Renewable energy scenarios - Awan, Kamran Yousaf; Rashid, Abdul (International Journal of Engineering and Technology, 2012)
Electricity is a basic need of the modern world. It is impossible for an economy to sustain without electricity. Pakistan, despite having the enormous energy resources, is facing acute shortage of Electricity. The Country’s electricity demand is rising at the rate of 11% annually, while incremental rate of production is fairly flat. Presently, only 15055MW of Electric Power is being generated while peak demand has reached up to 23953MW. Therefore, nation has to strive for meeting the deficiency of 8899 MW. Installed Power Generation Capacity of Pakistan is approximately 19,855 MW among which 67.2% is generated from thermal sources (oil and gas), 29.4% from hydel, 3.3% from nuclear and 0.1% from coal. Due to increased cost of petroleum products, slow development of hydel and nuclear power generation and negligible development of coal power generation, Country is facing severe electricity crisis. This article provides the overview of electricity shortage, problems associated with energy-mix used for power generation and root causes of electricity shortage in Pakistan. It also highlights the importance and availability of Pakistan’s indigenous energy resources, which can be economically used for electric power generation.